Knowledge about genetically modified food: a study with supermarket clients situated in noble area of Fortaleza city - doi:10.5020/18061230.2004.p72 - Paola Gondim Calvasina; Cíntia Maria Torres Rocha Silva; Gilka de Albuquerque Forte Aguiar; Milena Rebouças Aguiar; Helena Alves de Carvalho Sampaio (Universidade de Fortaleza, 2012)
The transgenic foods had appeared as result of the scientific and technological advances of genetic engineering applied to agriculture, configuring themselves in a current quarrel and sufficient controversy, about how much the benefits and curses brought to the consumers and the proper environment. In this intention, this study has as objective to verify the level of knowledge of customers of a supermarket of the noble area of the city of Fortaleza, on the thematic of the transgenic. Questionnaires structuralized with questions on transgenic foods with consumers of a situated supermarket in noble area of the city of Fortaleza in the period of March of 2003 had been applied. Sixty consumers had participated of the study who at the moment were making purchases in the supermarket. It was presented the end of the interview, to each consumer, a list of products, removed of the guide of the transgenic food consumer and not transgenic, available on the Greenpeace. In each list, people would have to recognize or not products of its habitual consumption. It was verified that 50% of the interviewed people had higher level of school knowledge, with 63,3% answering that they knew what transgenic foods are; 53,3% always look at the label during the purchase, being that the majority (76,7%) never saw, in the label, mention if the product is or not transgenic. It was evidenced, when interrogating on the possible risks to the health, that 33.3% find that they cause illnesses, however 51.7% would not be imported in consuming them. The opinion of the people regarding the release of these products is major (73,3%) in agreeing that the Federal Government must wait more research. From the list of products presented to the interviewed, 60% had told that they consume enter 5 to 9 products. It was evidenced that still a lack knowledge exists on the presence of transgenic in industrialized products, as well as how much to the risks consuming it. It has necessity of development of action of awareness of the group how much to the question of the right to the alimentary security